Linac-based stereotactic arrhythmia radioablation of paroxysmal atrial fibrillation in elderly patients. (3rd October 2022) - Di Monaco, A; Gregucci, F; Bonaparte, I; Troisi, F; Surgo, A; Di Molfetta, D; Vitulano, N; Romanazzi, I; Quadrini, F; Carbonara, R; Ludovico, E; Guida, P; et al.
Abstract: Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, occurring in 1–2% of the general population. Patients affected by AF have an increased risk of stroke and heart failure and European guidelines recommend catheter ablation of AF in symptomatic patients refractory to antiarrhythmic therapy. In elderly patients, the AF ablation procedure is associated with a higher rate of overall complications. Recently, stereotactic arrhythmia radioablation (STAR) with precise high-dose of radiation was used to treat ventricular arrhythmias. Purpose: No data were reported in literature about the use of Linac-based STAR, so a prospective phase-II trial was designed to evaluate safety of Linac-based STAR in elderly patients with paroxysmal AF. Methods: Fourteen patients (mean age 78±6 years; 57% male) were enrolled in the study. All patients had symptomatic paroxysmal AF refractory to antiarrhythmic drugs. All patients performed 1-week ECG-Holter monitoring (ECG-HM) and transthoracic echocardiogram before and after STAR. Primary end-point was defined as all the adverse events of special interest related to STAR treatment; secondary end-point was defined as AF recurrence after the treatment. The study was approved by the local Ethics Committee and all patients signed informed consent. Results: All patients performed STAR with a mean overall treatment time of 3 minutes. No serious adverse events were documented acutely and after 6 months of follow up. Transthoracic echocardiogram did not show cardiac damage after STAR. The 1-week ECG-HM performed before STAR documented symptomatic AF episodes in all patients. The 1-week ECG-HM performed 1-month after procedure documented frequent symptomatic atrial ectopy and atrial tachycardias without AF recurrences. The 1-week ECG-HM performed 3 and 6 months after procedure did not revealed AF recurrences. Two patients had a single episode of sustained atrial tachycardia 6 months after STAR. Both patients performed a left atrial mapping using CARTO system and Pentaray mapping catheter documenting PV isolation without vein stenosis (figure); no phrenic nerve damage was documented in both patients. All patients had an improvement in quality of life. Conclusion: Our preliminary data reported for the first time that the LINAC-based STAR approach could represent a valid alternative to perform PVI in elderly patients with paroxysmal AF. Funding Acknowledgement: Type of funding sources: None.